A Review: Effect of Heartwood Proportion in Wood Properties - Rizki Arisandi (Masyarakat Peneliti Kayu Indonesia, 2021)
This study aims to examine the effect of heartwood proportion on wood properties for construction materials by reviewing 98 journal articles and non-articles. The data were collected through an online search using seven keywords: heartwood proportion, heartwood effect, physical properties, mechanical properties, wood dimensional stability, wood gluing, and wood preservation. By eliminating the irrelevant papers, 45 journal articles and non-articles were selected. The review shows that the proportion of heartwood has a positive correlation with wood density and dimensional stability. High wood density will have a positive correlation with the mechanical properties of wood. However, the dimensional stability is not only affected by the proportion of the heartwood but also the microfibril angle and the arrangement of the wood cells. Further, sapwood has a higher moisture content than heartwood. The high moisture content causes the wood drying process to take longer and require more energy. However, it should be noted that the heartwood in some Acacia species has a higher moisture content than that in the sapwood, which is commonly called wet heartwood. Therefore, a suitable treatment is needed to minimize the moisture content in the heartwood. In addition, heartwood is difficult to preserve because of the high extractive content in the lumen. The color of the wood is another important indicator to determine the quality of wood, especially the heartwood color, because it is related to the aesthetic value and durability of the wood. Meanwhile, a better understanding of the acid and alkaline properties of extractive substances is necessary to perfectly conduct the wood gluing process.